Current Status of Core and Advanced Adult Gastrointestinal Endoscopy Training in Canada: Survey of Existing Accredited Programs - Xin Xiong; Alan N Barkun; Kevin Waschke; Myriam Martel; the Canadian Gastroenterology Training Program Directors (Canadian Journal of Gastroenterology)
OBJECTIVE: To determine the current status of core and advanced adult gastroenterology training in Canada.